Tidal controls on the flow of ice streams - Rosier, Sebastian; Gudmundsson, Hilmar (Geophysical Research Letters, 2016)
The flow of many Antarctic ice streams is known to be significantly influenced by tides. In the past, modeling studies have implemented the tidal forces acting on a coupled ice stream/ice shelf system in a number of different ways, but the consequences that this has on the modeled response of ice streams to tides have, until now, not been considered. Here we investigate for the first time differences in model response that are only due to differences in the way tidal forcings are implemented. We find that attempts to simplify the problem by neglecting flexural stresses are generally not valid and forcing models with only changes in ocean back pressure will not capture either the correct amplitudes or length scale.